HypomagnesemiaIs a Risk Factor of Febrile Seizure in Children - Hossain, Mir Mosharof; Chowdhury, Dhiman; Amin Chowdhury, Muhammad Jabed Bin; Chowdhury, Sourav Roy; Chowdhury, A N M Tanvir; Glory, Pandora; Das, Suparna (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Febrile seizure is a common pediatric emergency. This is the most common type of seizure in children aged 6 months to 6 years constituting 30% of all seizure types. Despite the high clinical burden of febrile seizure, little advance has been made in understanding its etiology. Magnesium deficiency is fairly common; clinicians rarely test for it in patients with febrile seizure. Hence this study is undertaken to find out whether low serum magnesium level is a risk factor of febrile seizure in children. The objective of the study was to determine the relationship of low serum magnesium level with febrile seizure. Materials and methods: This case-control study was conducted in Department of Pediatrics, Dhaka Medical College Hospital, Dhaka from January, 2019 to December, 2019. Forty-one children with febrile seizure enrolled as cases, along with similar number (Forty-one) of age and sex matched controls. Venous blood samples were obtained and analyses of serum magnesium levels were done. The results of cases and controls were compared. Data were analyzed through SPSS (version 25) software. Significance for the statistical tests (Chi Square test & unpaired t-test) were determined at a probability value of less than 0.05 (p<0.05). Results: Mean age of the respondents was 1.78±0.99 years in case and 1.48±0.94 years in control group. Family history of febrile seizure was present in 29.27% of the cases. Hypomagnesemia was noticed in 24.39% children with febrile seizure, on the other hand, 7.31% in controls and the difference was statistically significant. The Odds ratio was 4.08. Conclusion: serum magnesium was found to be significantly low in children with febrile seizure than that of febrile children without seizure. So, it may be concluded that low serum magnesium level can be regarded as a risk factor of febrile seizure in children. However further large-scale studies are needed to generalize the result of this study. JCMCTA 2023 ; 34 (1) : 21-24